2016
DOI: 10.21037/atm.2016.08.39
|View full text |Cite
|
Sign up to set email alerts
|

Blood loss in pelvic ring fractures: CT-based estimation

Abstract: Background:The main cause of mortality after pelvic ring fractures is the acute haemorrhagic shock. The aim of the study was to estimate blood loss using CT and to correlate estimated blood loss to the mortality.Methods: A retrospective analysis of 42 patients with AO/OTA C-type pelvic ring fractures was performed.In total 29 AO/OTA C1-type, 4 C2-type and 9 C3-type fractures were analysed. A CT-volumetric analysis was developed to estimate the early blood loss in the different compartments. The results were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Additionally, LC III fractures were shown to require over 105% of blood units transferred (0.7 units vs. 1.5 units) compared to LC II fractures. Veith et al presented, in their study, that the level of free blood volume found during the CT scan increases with the level of instability of the pelvic ring fracture in the AO/OTA C-types [26]. Not only does this support our findings, but it also indicates the importance of a thorough initial examination in order to establish the injury and associated injuries.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Additionally, LC III fractures were shown to require over 105% of blood units transferred (0.7 units vs. 1.5 units) compared to LC II fractures. Veith et al presented, in their study, that the level of free blood volume found during the CT scan increases with the level of instability of the pelvic ring fracture in the AO/OTA C-types [26]. Not only does this support our findings, but it also indicates the importance of a thorough initial examination in order to establish the injury and associated injuries.…”
Section: Discussionsupporting
confidence: 83%
“…Having said that, it is essential to acknowledge that the greater the displacement of the pelvic ring fracture, the higher the chance of severe bleeding and associated abdominal injuries [22,27]. The severity of the bleeding increasing with the instability of the pelvis is believed to be associated with the disruption of the sacral venous plexus and arterial branches of iliac vessels and the high amount of cancellous bone [26,27]. The presented results are in line with current knowledge that pelvic ring fractures can be mortal injuries that may require rapid intervention [14,[28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Given that patients are followed in the post-operative period, it may be possible to quantify return to function via measures such as force exerted via the joint repaired. In addition, one potential excellent outcome which may have been alluded to was decreased intraoperative blood loss compared to the traditional cohort, which is commonly used to as a parallel correlate to how invasive a procedure was ( 15 ). Moreover, from a clinical perspective, it is worth noting that the findings of this meta-analysis, while extremely sound, should ought to be used with additional considerations specific to the patient.…”
Section: Notable Future Directionsmentioning
confidence: 99%